Catalogue of type specimens of the agamid lizard genus Japalura s. l. (Squamata: Agamidae: Draconinae) - Denzer, Wolfgang; Manthey, Ulrich; Campbell, Patrick D (Zootaxa, 2019)
The genus Japalura Gray, 1853 s. l. currently comprises 34 species (Japalura n=7; Cristidorsa Wang, Deepak, Datta-Roy, Lin, Jiang, Che & Siler, 2018, n=2; Diploderma Hallowell, 1861, n=25). Furthermore the species Diploderma polygonatum is composed of its nominate form and three additional subspecies. For all but one species primary types (holo-, syn- or lectotypes) are available, and in most cases paratypical specimens have also been deposited. The type specimen of Japalura yunnannensis appears to be lost.